Rationality on the rise: Why relative risk aversion increases with stake size - Helga Fehr-Duda; Adrian Bruhin; Thomas F. Epper; Renate Schubert (University of Zurich, Socioeconomic Institute, 2008)
How does risk tolerance vary with stake size? This important question cannot be adequately answered if framing effects, nonlinear probability weighting, and heterogeneity of preference types are neglected. We show that, contrary to gains, no coherent change in relative risk aversion is observed for losses. The increase in relative risk aversion over gains cannot be captured by the curvature of the utility function. It is driven predominantly by a change in probability weighting of a majority group of individuals who exhibit more rational probability weighting at high stakes. These results not only challenge expected utility theory, but also prospect theory.
Keywords: 330; Entscheidung bei Risiko; Risikoaversion; Erwartungsnutzen; Prospect Theory; Test